Online Marketing Education and Application Development for MSMEs in Buah Batu District Bandung - Wulandari, Astri; Suryawardani, Bethani; Marcelino, Dandy; Satrya, Gandeva Bayu; Prawita, Fat’hah Noor; Febrianta, Mochamad Yudha (Jurnal Penyuluhan, 2022)
In today's fast-paced world of information and technology, it's impossible to do anything without a connection to the internet. Due to the rising level of competition in the market, small and medium-sized businesses (SMEs) that are owned and operated by business people need to make use of digital media to raise their brands' visibility and hence their competitiveness. In order to help MSME actors in Buah Batu District continue to grow and develop, the mentorship program for selected partners aims to assist them in developing innovative goods. The MSME actors in Buah Batu District are likely to benefit from assistance related to the district's online web platform, which has been established. It has been determined that in order to help MSME actors (including those designing product labels and packaging) learn about online marketing, the team will offer online marketing education workshops. They will also develop a better product website, integrate the site with helpful applications, and create an updated database system that can be relied upon.